Diseño hidráulico y estructural del sistema de drenaje pluvial urbano del sector progreso margen izquierda quebrada Choclino, en la banda de Shilcayo Tomo I - Delgado Ramírez, José Fernando (2003)
Population growth accelerated in most cities across the country in recent years, it has resulted in increased demand for more and better public services, among which are especially important surplus rainwater; · known as storm drainage urban. The thesis project called: HYDRAULIC DESIGN AND STRUCTURAL SYSTEM STORMWATER URBAN PROGRESS SECTOR - LEFT BANK BROKEN CHOCLINO IN THE BAND Shilca I, seeks to provide comprehensive solution to the serious problems • progressive deterioration of grazing on public roads , platforms existing arts works, occurring in progress in the city of Band Shilcayo sector; when ordinary and extraordinary rainfall occur. In this thesis, has made tcpográficos uprisings in the current urban area (45.64 ha.), Information that allowed us to get the project plans. Topographic maps · (manzaneo and contour lines) allows us to define a total drain of 45.64 Ha area., Which has been divided into 31 collecting areas, within which have been identified 77 tax areas, see map collector P AC Areas . the design flow was determined using the Rational methods and Mac Mat: h, depending on the runoff coefficient, collecting areas, slope, the design intensity corresponding to a time of return Tr = 25 years. With the design flow, slope and roughness, we calculate the geometry of the sections of each stretch of collector, the same that make its final delivery planned at the end of 08 works deliveries planned and located in the channel of the Quebrada structures Choclino , see map PPH. This work will form the basis for the execution of works of urban storm drainage, the same as his running short and medium term arises, by the magnitude of the costs of construction.The thesis work "HYDRAULIC DESIGN AND STRUCTURAL SYSTEM URBAN DRAINAGE SECTOR PROGRESS -MARGEN CHOCLINO BROKEN LEFT iN tHE BAND SHILCAYO "was held as a contribution to the approval of the National University of San Martin - Faculty of Civil Engineering, for the District Municipality of Shilcayo Band. The thesis work "HYDRAULIC DESIGN AND STRUCTURAL SYSTEM STORMWATER URBAN SECTOR PROGRESS LEFT BANK BROKEN CHOCLINO IN THE BAND SHILCAYO" was held as a contribution to the approval of the National University of San Martin - Faculty of Civil Engineering for the District Municipality Band Shilcayo.